Role of Lumbini Buddhist University in Nepal- China Relations - Shrestha, Tara Lal (Journal of Advanced Research in English & Education; Vol 8 No 1 (2023): Journal of Advanced Research in English & Education, 2023)
Buddha is an international brand. Nepal-China relations continued from ancient times through cultural exchange related to Buddhism. Buddhist philosophy, literature, culture are attracting the international community. This paper attempts to explore how Lumbini Buddhist University could play a role to connect the international community with reference to Nepal-China relations. It explores the situation of the academic exchange programs between Nepal and China through LBU. This research- in the era when capitalism is killing our root values- also attempts to present some ways to sustain the spiritual essence related to Buddhism via LBU.